Degradation Of Amoxicillin In Aqueous Solution By Nano-MgO/UV Photocatalytic Process: Pharmaceutical Science-Pharmaceutical analysis for Novel drug formulation - Ferdos Kord Mostafapour; Davoud Balarak; Kethineni Chandrika (International Journal of Life Science and Pharma Research, 2022)
Antibiotics, an important type of pharmaceutical product, have attracted many researchers to the study of their removal from aqueous solutions for certain reason. Although the amount of pharmaceuticals in the aquatic environment is low, its continuous input may constitute in the long term potential risk for aquatic and terrestrial organisms. Therefore, over the past few years these compounds are considered to be an emerging environmental problem. In this study, the effects of some operational factors on the degradation efficiency of Amoxicillin (AMO) in aqueous solution were discussed through photocatalytic experiments using Magnesium oxide (MgO) as the photocatalyst. The experiments were carried out by irradiating the aqueous solutions of AMO containing photocatalysts with UV light. Similar experiments were carried out by varying pH (3–11), amount of catalyst (0.1–1 g/L) and initial concentration of AMO (10–100 mg/L) at irradiation time between 10 and 120 min. The experimental results indicated that the maximum degradation of AMO occurred at basic pH and the maximum degradation of AMO was noticed at pH 11. The percentage reduction of AMO was estimated under UV system and it was found that AMO reduction takes place at a faster rate under UV light as compared to darkness. The results indicated that the optimal conditions for the process were the irradiation time of 60, amount of catalyst of 0.6 g/L and AMP concentration of 10 mg/L, which resulted in the maximum efficacy of 100%. In addition, the findings indicated that the process had outstanding efficiency in the removal of the AMO antibiotics.